The Profile of Reproductive Age Women Causes of Low Birth Weight (LBW) Baby Incidence in South East Asia 2005-2014 - Laras Sitoayu; Nanda Aula Rumana (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
Low birth weight (LBW) accounts for the highest percentage of causes of neonatal death. The purpose of this study was to identify family profiles that influence the incidence of LBW throughout Southeast Asia. The sample in this study were women aged 19-29 years. The data used were secondary data published by Measure Demografic Health Survey (DHS) in 2005-2014. Women's profiles identified included maternal factors (area of residence, education, age, economic status, marital status, parity, location of delivery), health service factors (iron consumption, pregnancy visit / ANC). The results showed that the incidence of LBW occurs a lot with the profile of respondents who have rural areas, even though they have high economic status. Most respondents who gave birth to LBW had secondary and low education, with unmarried marital status and low partner education. In addition, there were still many respondents who were not obedient to antenatal visits and consume less iron. However, some had given birth at local health services, although there were still respondents who had a lot of parity. Researchers suggest that women, especially women of childbearing age, want to pay attention to the risk factors for the incidence of LBW, including consumption of iron and delivery in health services so that the incidence of LBW can be suppressed. Keyword: family profile, Southeast Asia, LBW, women of childbearing age